Da'wah and Counter-Radicalism in Indonesia - Mukhtidinov, Rashid (Institut Agama Islam Syarifuddin Lumajang, 2023)
This article discusses the urgency of da'wah in counterradicalism efforts in Indonesia. Preachers must have a precise strategy to address the potential for radicalism which can lead to acts of terror in Indonesia. Da'wah is an activity that calls for, invites and summons people to believe and obey Allah, Lord of the Worlds in accordance with Islamic beliefs, morals and Shari'a with full awareness and in a planned manner. The main purpose of da'wah is to be able to achieve happiness in the world and in the hereafter. Da’wah on counter-radicalism is urgent. As a large country, both in terms of population and area, the Muslim community in Indonesia, which is the majority, has many different views. diverse streams become diverse. The form of Islam in Indonesia has become very diverse. This diversity is reflected in the number of Islamic organizations and interest groups acting in the name of Islam which are increasingly varied from time by time. This study uses qualitative methods. The approach used is literature review. The data discussed are based on sources from books, journal articles, and other documentation relevant to the topic of da'wah and counter-radicalism. The results of this study show the urgency of preaching with various methods, in order to spread good messages. Including, messages regarding counter-radicalism. Efforts to prevent radicalism must be intensified. This study can provide theoretical and practical benefits for counter-radicalism efforts in Indonesia. On the one side, this article can add to the body of research on da'wah and counter-radicalism. On the other hand, the results of this study can be used as material for consideration for practitioners in running counter-radicalism programs